2015
DOI: 10.1016/j.ijwd.2015.02.001
|View full text |Cite
|
Sign up to set email alerts
|

The effect of probiotics on immune regulation, acne, and photoaging

Abstract: Probiotics are live micro-organisms that provide a health benefit to the host. The role of probiotics in the management of disease, as well as immune modification, has recently experienced a renewed interest in society, as probiotics can be found in products ranging from yogurt to facial creams. In this article, we discuss the role of probiotics in the development of the immune system, the treatment of acne and rosacea, and protection against aging and photodamage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
104
0
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(123 citation statements)
references
References 62 publications
0
104
0
9
Order By: Relevance
“…In vitro studies have shown the capacity of probiotics, such as Streptococcus salivarius and Enterococcus faecalis, to directly inhibit P. acnes growth through antibacterial proteins’ production, as detailed in this article. An example of antibacterial protein is the Bacteriocin‐like inhibitory substance (BLIS), which can cause significant inhibition in the growth of P. acnes . Additionally, its immunomodulatory effects in keratinocytes and epithelial cells suggest a physiological mechanism to support its use as adjuvant in acne treatment .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro studies have shown the capacity of probiotics, such as Streptococcus salivarius and Enterococcus faecalis, to directly inhibit P. acnes growth through antibacterial proteins’ production, as detailed in this article. An example of antibacterial protein is the Bacteriocin‐like inhibitory substance (BLIS), which can cause significant inhibition in the growth of P. acnes . Additionally, its immunomodulatory effects in keratinocytes and epithelial cells suggest a physiological mechanism to support its use as adjuvant in acne treatment .…”
Section: Resultsmentioning
confidence: 99%
“…An example of antibacterial protein is the Bacteriocin‐like inhibitory substance (BLIS), which can cause significant inhibition in the growth of P. acnes . Additionally, its immunomodulatory effects in keratinocytes and epithelial cells suggest a physiological mechanism to support its use as adjuvant in acne treatment . Probiotics show potential for direct and indirect benefits in the condition's treatment: directly by inhibiting P. acnes growth and decreasing the characteristic inflammatory response, and indirectly by softening side effects from current treatments.…”
Section: Resultsmentioning
confidence: 99%
“…However, as the pathophysiological mechanisms and underlying processes of the disease advance, new targets emerge for the treatment of AD [5]. Recent studies suggest that the use of probiotics provides benefits in terms of skin health and can help to prevent AD [20][21][22]. Similarly, non-viable bacterial derivatives have been shown to exert antimicrobial and immunomodulating action and can elicit certain immune responses on the skin and improve skin barrier functions [23].…”
Section: Introductionmentioning
confidence: 99%
“…These results illustrate the limits of this system, which need to be addressed for a clinical application. While the currently described system is unsuitable for application inside the body, it could be acceptable for skin‐based therapies and cosmetics that would also be able to utilize light‐responsive properties most effectively. Modifying the system to produce other drugs such as cinnamaldehyde and carbapenem that have shown to be optimally synthesized at 37 °C in E. coli and secreted without the requirement of solubilizers could be considered for in vivo clinical applications.…”
mentioning
confidence: 99%